Servant Leadership Strengthening Modeling - Hermawan, Andi; Setyaningsih, Sri; Hardhienata, Soewarto (Universitas Pakuan, 2022)
Principals as school leaders are a contributing factor to success in efforts to strengthen governance, accountability, and public image. This success cannot be separated from competence and ability in their duties, roles and functions. Providing excellent service to all school members, optimizing the empowerment and development of school residents, focusing on performance and growth and impact for school progress and for the community, this leadership is called servant leadership. This study aims to produce a model of strengthening service leadership in the form of a constellation model of influence between variables and their mathematical model. From this model, a research hypothesis is derived which will then be tested using path analysis at the quantitative research stage. The research begins by interviewing informants who are considered competent in providing the expected answers. Furthermore, data reduction, data codification, data display, data analysis, and conclusion drawing were carried out. The research was carried out at the Bogor Regency Private Vocational School in the period October to December 2020. From the research conducted, several variables are thought to have positive and dominant influence on service leadership, namely adversity intelligence, proactive personality, teamwork as exogenous variables, organizational commitment, and work motivation as intervening variables.